Heterogeneous CuxO Nano-Skeletons from Waste Electronics for Enhanced Glucose Detection - Pan, Yexin; Yu, Ruohan; Jiang, Yalong; Zhong, Haosong; Yuan, Qiaoyaxiao; Lee, Connie Kong Wai; Yang, Rongliang; Chen, Siyu; Chen, Yi; Poon, Wing Yan; Li, Mitch Guijun (Nano-Micro Letters, 2024)
Electronic waste (e-waste) and diabetes are global challenges to modern societies. However, solving these two challenges together has been challenging until now. Herein, we propose a laser-induced transfer method to fabricate portable glucose sensors by recycling copper from e-waste. We bring up a laser-induced full-automatic fabrication method for synthesizing continuous heterogeneous CuxO (h-CuxO) nano-skeletons electrode for glucose sensing, offering rapid (< 1 min), clean, air-compatible, and continuous fabrication, applicable to a wide range of Cu-containing substrates. Leveraging this approach, h-CuxO nano-skeletons, with an inner core predominantly composed of Cu2O with lower oxygen content, juxtaposed with an outer layer rich in amorphous CuxO (a-CuxO) with higher oxygen content, are derived from discarded printed circuit boards. When employed in glucose detection, the h-CuxO nano-skeletons undergo a structural evolution process, transitioning into rigid Cu2O@CuO nano-skeletons prompted by electrochemical activation. This transformation yields exceptional glucose-sensing performance (sensitivity: 9.893 mA mM−1 cm−2; detection limit: 0.34 μM), outperforming most previously reported glucose sensors. Density functional theory analysis elucidates that the heterogeneous structure facilitates gluconolactone desorption. This glucose detection device has also been downsized to optimize its scalability and portability for convenient integration into people’s everyday lives. Highlights: 1 Novel laser-induced transfer method for fabricating glucose sensors from recycled e-waste copper, offering a sustainable and cost-effective solution. 2 Unique heterogeneous CuxO nano-skeletons derived from discarded printed circuit boards exhibiting exceptional glucose-sensing performance (sensitivity: 9.893 mA mM−1 cm−2, detection limit: 0.34 μM). 3 Miniaturized glucose detection device, optimized for scalability and portability, revolutionizing diabetes management and patient care.